Education, sectoral choice and the urban-rural welfare gap in Sri Lanka - Bandara, Nirodha Anuththari (2017)
This thesis is centred on three core issues in the context of Sri Lanka - the rates of returns to education across individuals in different types of employment, the contributors towards the urban-rural welfare gap for the years 2002 and 2009/10, and finally the determinants of employment and earnings across sectors.